2018
DOI: 10.1080/13574809.2018.1440176
|View full text |Cite
|
Sign up to set email alerts
|

Articulating a social-ecological resilience agenda for urban design

Abstract: In an era of change and uncertainty, the need for resilience is high on urban agendas. To date, multiple resilience concepts have been adopted into urban design with minimal substantiation. Resilience theory can potentially improve practice by rebalancing contemporary discourses in order to better value procedural aspects of urban design. The paper establishes theoretical links between urban design and resilience, where the integration of social and ecological systems, and the ability to enable adaptability an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 102 publications
(162 reference statements)
0
11
0
1
Order By: Relevance
“…A community's social capital relies on involvement, mutual assistance, trust and social cohesion (Adger et al, 2005;Folke et al, 2005;Quigley et al, 2018;Rusch, 2010). Past research has also shown that smaller groups are more successful in the management of the commons, thanks to more frequent interactions and higher levels of trust (Nagendra & Ostrom, 2014;Poteete & Ostrom, 2004;Rogge et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A community's social capital relies on involvement, mutual assistance, trust and social cohesion (Adger et al, 2005;Folke et al, 2005;Quigley et al, 2018;Rusch, 2010). Past research has also shown that smaller groups are more successful in the management of the commons, thanks to more frequent interactions and higher levels of trust (Nagendra & Ostrom, 2014;Poteete & Ostrom, 2004;Rogge et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This definition is in line with the one given by Lumineau and Malhotra (2011), who highlight a vulnerability to the actions of others, given positive expectations on why and how they could perform. Finally, the sense of cohesion is a measure of the group ability to bond and potentially engage in meaningful collaboration (Quigley et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Quinlan et al [34] Diversity and redundancy, connectivity, feedback, learning and experimentation, participation, polycentric governance Quigley et al [11] Diversity, social capital, innovation, learning…”
Section: Source Resilience Propertiesmentioning
confidence: 99%
“…The ecological perspective that emphasizes persistence and change to maintain basically the same structure, function, and identity is used in hazard management and ecosystem conservation. The social-ecological perspective that focuses on dynamic interactions between social and ecological systems across multiple temporal and spatial scales is widely considered key to building adaptive capacity and transformability in the broad context of social-ecological systems [11][12][13]. The integrative and vague essence of urban resilience makes it a malleable concept, which is beneficial from multiple perspectives for the evolution to a desirable development trajectory by embracing the ability to change as flexibly as possible over time [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Abordar questões ambientais como o contexto da qualidade da água em áreas urbanas dentro da perspectiva das ferramentas do design pode oferecer diversas vantagens (QUIGLEY et al, 2018). A pesquisa através do design permite que haja uma concepção holística da situação, agrupando o contexto, tecnologia, necessidades humanas, empatia com a visão dos usuários e tomadores de decisão a fim de criar soluções e produtos que atinjam diferentes objetivos de forma simultânea (MAHER et al, 2018).…”
Section: Inovação Na áRea Ambiental E No Planejamento Urbanounclassified